Development of a Hyaluronic Acid-Based Nanocarrier Incorporating Doxorubicin and Cisplatin as a pH-Sensitive and CD44-Targeted Anti-Breast Cancer Drug Delivery System - Yu, Tao; Li, Yongshuang; Gu, Xueyuan; Li, Qin (Frontiers in Pharmacology, 2020)
Tumor-targeting chemotherapeutic drug delivery systems using nano-materials are certified to be an efficacious approach for cancer treatment due to their stable delivery pattern in blood circulation, enhanced tumor-selective drug accumulation and decrease of toxicity on normal tissues. CD44 is a transmembrane glycoprotein overexpressed in various human tumors including breast, ovarian, lung and stomach, and known to bind hyaluronic acid (HA) in its extracellular domain. In this study, an HA-based nano-carrier incorporating doxorubicin (DOX) and cisplatin (CDDP) was synthesized as a CD44-targeting anti-carcinogen, and its tumor inhibition effects against CD44+ breast cancer cells was evaluated both in vitro and in vivo. The dual drug loaded HA micelle (HA-DOX-CDDP) exhibited significantly enhanced drug release under acid condition. Compared to free drugs, stronger cellular uptake and higher cellular growth inhibition were detected in HA-DOX-CDDP treated 4T1 (CD44+) breast cancer cells, while no significant difference in NIH-3T3 (CD44-) normal cells. Furthermore, HA-DOX-CDDP micelle also exhibited greater inhibition effects and lower systemic toxicity than free drugs in 4T1 mammary cancer bearing mouse models, which was confirmed by immunofluorescence and histological analyses. Therefore, HA-DOX-CDDP micelle as a promising drug delivery system revealed acid-sensitive drug release, CD44-targeted delivery profile, excellent biocompatibility and biodegradation, leading to valid site-tumor accumulation and diminished adverse effects, and possessing the great potential application in breast cancer chemotherapy.